Impact of psychological dimensions of psychosomatic status on potential competitive performance in cross-country skiing - Cernohorski, B.; Pustovrh, J.; Tusak, M. (Kinesiology, 2006)
The purpose of the study was to establish the values of the variables of the psychological area in predicting the potential competitive performance of cross-country skiers. The psychological area, encompassing 24 variables, was studied within the model of potential performance MMPS. The sample consisted of 48 cross-country skiers of three competitive categories. The expert modelling procedure was used to obtain the scores of the potential performance of the subjects at all levels of the psychological area. An analysis of correlation between these scores and the actual competitive performance criterion (SLO_FIS) showed that the psychological area in all three competitive categories of subjects was differently but statistically insignificantly correlated with their competitive performance. The average scores of individual psychological dimensions increase gradually with the subjects` chronological age, however, there are some deviations pos-sibly resulting from the not yet stabilised psychological structures. The monitoring of the average scores of the subjects` potential competitive performance in terms of psychological variables by different age category can predict a regular development trend in the psychological make-up of cross-country skiers.